Case Report: A Novel Pathogenic Missense Mutation in FAS: A Multi-Generational Case Series of Autoimmune Lymphoproliferative Syndrome - Gaefke, Claudia L.; Metts, Jonathan; Imanirad, Donya; Nieves, Daime; Terranova, Paola; Dell'Orso, Gianluca; Gambineri, Eleonora; Miano, Maurizio; Lockey, Richard F.; Walter, Jolan Eszter; Westermann-Clark, Emma (Frontiers in Pediatrics, 2021)
Autoimmune Lymphoproliferative Syndrome (ALPS), commonly caused by mutations in the FAS gene, is a disease with variable penetrance. Subjects may be asymptomatic, or they may present with lymphadenopathy, splenomegaly, cytopenias, or malignancy. Prompt recognition of ALPS is needed for optimal management. We describe a multi-generational cohort presenting with clinical manifestations of ALPS, and a previously unreported heterozygous missense variant of unknown significance in FAS (c.758G>T, p.G253V), located in the death domain of exon 9. Knowledge of the underlying genetic defect permitted prompt targeted therapy to treat acute episodes of cytopenia. This cohort underscores the importance of genetic testing in subjects with clinical features of ALPS and should facilitate the reclassification of this variant as pathogenic.